2013
DOI: 10.1037/cpp0000020
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a family-based intervention (FBI) for overweight/obese children on health and psychological functioning.

Abstract: Obesity is the most prevalent chronic disease in childhood. There are many comorbidities associated with excess weight that are preventable with improved health. Prevention of medical comorbidities associated with obesity is critical and should begin early, particularly in childhood and preadolescence. This article examined immediate post-treatment and follow-up results of a randomized controlled trial of a 6-month lifestyle intervention involving diet, education, physical exercise, behavior change, and psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 30 publications
0
23
0
1
Order By: Relevance
“…61 Four trials reported follow-up data (6-12 mo postintervention). 32,41,57,60 Meta-analysis showed significantly lower BMI and BMI z-score in the intervention group compared with the control group by the end of treatment (Table 3). However, there was no difference in BMI and BMI z-score between groups at the time of postintervention to 1-year follow-up.…”
Section: Cmaj Openmentioning
confidence: 99%
See 1 more Smart Citation
“…61 Four trials reported follow-up data (6-12 mo postintervention). 32,41,57,60 Meta-analysis showed significantly lower BMI and BMI z-score in the intervention group compared with the control group by the end of treatment (Table 3). However, there was no difference in BMI and BMI z-score between groups at the time of postintervention to 1-year follow-up.…”
Section: Cmaj Openmentioning
confidence: 99%
“…Eleven interventions involved group sessions, 5 used individual sessions, and almost all interventions (n = 12) incorporated parental or family involvement. 32,35,36,41,48,49,51,[53][54][55]58,60 Three interventions used technology to facilitate interaction between participants and study personnel or as a means of delivering information or encouraging physical activity. Duration of interventions ranged from 3 months to 2 years.…”
Section: Features Of Efficacious Interventionsmentioning
confidence: 99%
“…Mazzeo et al (2014) utilized a parent-only approach and found that 6 or 12 90-minute sessions (duration was adjusted during treatment) resulted in a loss of 0.28 BMI percentile points in the intervention group, which represented a small but significant decrease in BMI percentile compared to the control group, which did not experience any weight changes ( d =0.11) (34). Lochrie et al (2013) used 14 sessions across a longer time period (6 months) and found a reduction in zBMI of 0.13 in the intervention group, but a negligible loss of 0.03 zBMI points in the control group ( d =0.31) (35). A unique approach by Morgan et al (2013) which primarily targeted fathers’ weight, but had secondary aims to improve child lifestyle behaviors, also was successful in producing significantly improved zBMI weight outcomes (loss of 0.18 points) compared to a wait-list control group (loss of 0.08 points) ( d =0.10) (36).…”
Section: Weight Outcomesmentioning
confidence: 99%
“…A recent systematic review of obesity-related randomized controlled trials conducted with Hispanic youth aged 5–19 years old identified 11 interventions published between 2010–2015, the majority of which (72%) included some sort of family-based component [ 13 ]. Although family-based pediatric weight loss studies have been found to successfully reduce youth BMI [ 14 ], stronger effects are often detected in those with higher versus lower rates of attendance [ 15 , 16 , 17 ]. Notably, poor attendance in both clinical and research settings has been cited as one of the most common challenges of pediatric obesity interventions, with the highest rates of attrition observed among low income and ethnic minority populations [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%